Religion and the demographic revolution: women and secularisation in Canada, Ireland, UK and USA since the 1960s - Brown, Callum G. (Boydell & Brewer, 2012)
In the 1960s, two great social and cultural changes of the western world began. The first was the rapid decline of Christian religious practice and identity and the rise of the people of 'no religion'. The second was the transformation in women's lives that spawned a demographic revolution in sex, family and work. Both phenomena were sudden though not uniform in their impact. The argument of this book is that the two were intimately connected, triggered by an historic confluence of factors in the 1960s. Canada, Ireland, UK and USA represent different stages of secularisation for the book's study. The religious collapse in mainland Britain and most of Canada was sharp and spectacular but contrasted with the more resilient religious cultures of the United States, the Canadian Maritimes, Ireland and Northern Ireland. Using statistical evidence from government censuses, the book demonstrates how secularisation was deeply linked to demographic change. Starting with the distinctive features of the 1960s, the book quantifies secularisation's scale, timing and character in each nation. Then, the intense links of women's sexual revolution to religious decline are explored. From there, women's changing patterns of marriage, coupling and birthing are correlated with diminishing religiosity. The final exploration is into the secularising consequences of economic change, higher education and women's expanding work roles. This book transforms the way in which secularisation is imagined. Religion matters more than mere belief, practice and the churches; it shapes how populations construct their sexual practices, families and life-course. In nations where religion has been dissolving since 1960 into apathy and atheism, the process has been part of a demographic revolution built on new moral codes. Connecting religious history with the history of population, this volume unveils how the historian and sociologist need to engage with the demographic enormity of the decline of Christendom. CALLUM G. BROWN is Professor of Religious and Cultural History at the University of Dundee.